Complement Component C1q as an Emerging Biomarker for the Diagnosis of Tuberculous Pleural Effusion - Qiao, Xin; Shao, Ming-Ming; Yi, Feng-Shuang; Shi, Huan-Zhong (Frontiers in Microbiology, 2021)
Background and objective The accurate differential diagnosis of tuberculous pleural effusion (TPE) from other exudative pleural effusions is often challenging. We aimed to validate the accuracy of complement component C1q in pleural fluid (PF) in diagnosing TPE. Methods The level of C1q protein in the PF from 49 patients with TPE and 61 patients with non-tuberculous pleural effusion (non-TPE) was quantified by enzyme-linked immunosorbent assay, and the diagnostic performance was assessed by receiver operating characteristic (ROC) curves based on the age and gender of the patients. Results The statistics showed that C1q could accurately diagnose TPE. Regardless of age and gender, with a cutoff of 6,883.9 ng/mL, the area under the curve (AUC), sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of C1q for discriminating TPE were 0.898 (95% confidence interval: 0.825 to 0.947), 91.8 (80.4 to 97.7), 80.3 (68.2 to 89.4), 78.9 (69.2to 86.2), and 92.5 (82.6 to 96.9), respectively. In subgroup analysis, the greatest diagnostic accuracy was achieved in the younger group (≤ 50 years of age) with an AUC of 0.981 (95% confidence interval: 0.899 to 0.999) at the cutoff of 6,098.0 ng/mL. The sensitivity, specificity, PLR, NLR, PPV, and NPV of C1q were 95.0 (83.1 to 99.4), 92.3 (64.0 to 99.8), 97.4 (85.2 to 99.6), and 85.7 (60.6 to 95.9), respectively. Conclusion Complement component C1q protein was validated by this study to be a promising biomarker for diagnosing TPE with high diagnostic accuracy, especially among younger patients.